The Influence of Organizational Commitment, Work Environment, Work Discipline, and Motivation on Employee Performance in Manufacturing and Assembly of Electronic Components - Elfina, Rini; Sumardin; Tanjung, Rona (MultiTech Publisher, 2024)
This research aims to determine and analyse the influence of Organizational Commitment, Work Environment, Work Discipline and Motivation. This type of research is quantitative with a population of 76 respondents. Questions are given using a questionnaire with the Google Form technique. The data analysis methods used are Descriptive Test, Validity Test, Reliability Test, Classical Assumption Test, Multiple Analysis and Determination (????2). The results of data analysis using multiple regression and hypotheses using the SPSS program and it can be seen that Organizational Commitment has a significant effect on employee performance, Work Environment does not have a significant effect on employee performance, Work Discipline has a significant effect on employee performance, Motivation has a significant effect on employee performance, and systematic testing Simultaneously shows that Organizational Commitment, Work Environment, Work Discipline and Motivation have a significant effect on Employee Performance.